DEVELOPMENT OF POWERPOINT-BASED KARIRO LEARNING MEDIA ON STRAIGHT LINE EQUATIONS - Robiyanto, Ahmad; Sari, Astrid Chandra; Cindarbumi, Festian (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
There is a lack of interest among students at SMP Plus Al Amanah in mathematics lessons, so a new learning method is needed, namely the use of learning media in the teaching and learning process. hoped that KARIRO's power point-based learning media on straight line equations can help educators convey material to students. This type of research is research and development or what is commonly known as R&D. R&D research is a type of research that produces a product. The assessment of the development of KARIRO learning media based on Power Point on Straight Line Equations was carried out by media experts, obtaining a percentage of 80%, which was stated in the Valid criteria, by material experts, a percentage of 94% was obtained, which was stated in the Very Valid criteria. Validation by the Mathematics subject teacher at SMP Plus Al-Amanah Dander, obtained a percentage of 92.3% which was declared to be very valid criteria. The feasibility test carried out at SMP Plus Al-Amanah by 30 students obtained a percentage of 92.1% of KARIRO learning media products which were declared to be very feasible.